The Polish-Soviet war in the Norwegian press during the years 1920–1921 - Siemianowski, Jordan (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2023)
During the Polish-Soviet war, it was common knowledge then that the conflict in question had a considerable influence on the Mid- and West European states. It was expected that, were the Red Army to have won, the Soviet revolution would have spread as far as the Marne. The reason why the conflict in question was of so much interest to the Norwegian press was that it reflected Norwegian public opinion regarding the position of the then superpowers towards the war, showing how Norwegian public opinion understood this war, as well as Norwegians’ sympathy for or disfavour towards the militant parties. This article aims both at presenting the above-mentioned issues and juxtaposing them with the political, military, and social questions to date as they appeared in the then Norwegian press. For that purpose, my article will also refer to the literature about the Polish-Soviet war.